Statins enhance trastuzumab deruxtecan efficacy: Preclinical synergy in HER2-negative models and clinical benefit in HER2-positive metastatic breast cancer - Sahin, T.; Orhan, C.; Ozercan, I; Muglu, H.; Er, B.; Akyildiz, A.; Guven, D. (Amer Assoc Cancer Research, 2026)
[Abstract Not Available]